Ethanol solution sensor based on ZnO/PSi nanostructures synthesized by catalytic immersion method at different molar ratio concentrations: an electrochemical impedance analysis - Husairi, F.S.; Rouhi, J.; Eswar, K.A.; Ooi, Chong Heng Raymond; Rusop, M.; Abdullah, S. (Elsevier, 2015)
ZnO-based electrochemical impedance sensors are expected to play an increasing role in environmental monitoring, and recent technological advances are certain to facilitate the application of chemical-sensing devices. In this work, ZnO was successfully synthesized on porous Si (PSi) substrates by catalytic immersion method to study an ethanol-solution sensor. The structural and optical properties of ZnO/PSi nanostructures were characterized using photoluminescence, X-ray diffraction (XRD) spectroscopy, and field-emission scanning electron microscopy (FESEM). Sensing performance was examined by a simple and reliable electrochemical impedance spectroscopy (EIS) technique. FESEM images indicated that PSi pores were filled by small particles with uniform grain size with increased stabilizer concentration. At higher concentrations, a slight position shift of XRD peaks to a lower angle occurred, and this finding may be due to decreased tensile stress in ZnO thin films. Results showed excellent performance in sensor response to ethanol solution at stabilizer concentration of 0.4M which can be attributed to the high concentration of oxygen defects in the form of interstitial oxygen and deep-level defects introduced into the film. (C) 2015 Elsevier B.V. All rights reserved.